2010
DOI: 10.1111/j.1365-2486.2010.02169.x
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal changes in at‐sea distribution and abundance of subantarctic seabirds along a latitudinal gradient in the Southern Indian Ocean

Abstract: Long‐term demographic studies have recently shown that global climate change together with increasing direct impacts of human activities, such as fisheries, are affecting the population dynamics of marine top predators. However, the effects of these factors on species distribution and abundance at sea are still poorly understood, particularly in marine ecosystems of the southern hemisphere. Using a unique long‐term data set of at‐sea observations, we tested for interdecadal (1980s vs. 2000s) changes in summer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 84 publications
5
56
0
Order By: Relevance
“…T. chlororhynchos presented low frequency of occurrence (FO <4.00%) in the Indian Ocean (Péron et al, 2010), whereas in the Atlantic Ocean, on the Brazilian coast, high frequency of occurrence (FO = 58.82%) was found for this species. e di erences in abundance of some species between the sampled years might be explained by variations in the distance of the observers Latitude 29° S showed the largest abundance of seabirds with 41 individuals, although the highest richness was observed at latitudes 26° S e 30º S, with ve species in each from the coast, depth, water temperature, atmospheric pressure, and wind speed (Krüger & Petry, 2011) which were not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…T. chlororhynchos presented low frequency of occurrence (FO <4.00%) in the Indian Ocean (Péron et al, 2010), whereas in the Atlantic Ocean, on the Brazilian coast, high frequency of occurrence (FO = 58.82%) was found for this species. e di erences in abundance of some species between the sampled years might be explained by variations in the distance of the observers Latitude 29° S showed the largest abundance of seabirds with 41 individuals, although the highest richness was observed at latitudes 26° S e 30º S, with ve species in each from the coast, depth, water temperature, atmospheric pressure, and wind speed (Krüger & Petry, 2011) which were not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many species are long-range migrants, with their routes over the South American countries still under studied by marine ornithologists. Long-term demographic studies have recently shown that climate change, together with direct impacts of human activities (such as overfishing, bycatch, and pollution), are affecting population dynamics of marine top predators, including seabirds (Ormerod 2003, Ramos et al 2009, Péron et al 2010a, 2010b. Consequently, studies on seabirds migration routes over oceanic areas and coastal lands are very important for conservation and management plans.…”
Section: Introductionmentioning
confidence: 99%
“…Seabirds are important components of the marine ecosystems and are the most studied taxa in relation to long-term demographic studies on land (Weimerskirch 1997, Péron et al 2010a, 2010b. However, ecological studies in open ocean areas are rare, since logistic procedures to support field works are exceedingly difficult (Tasker et al 1984, Weimerskirch 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Important components of the marine ecosystem, seabirds are widely distributed and have large migratory movements (Péron et al, 2010). Some species are recorded using the South Atlantic region as a resting and foraging area.…”
Section: Introductionmentioning
confidence: 99%